Respuesta :

Answer:

C

Step-by-step explanation:

If this was an equation...

(x-3)(x+5) = 0

x = 3, -5

So 3 and -5 are the minimum and the maximums.

So we convert that into an inequality.

-5 <= x <= 3

For this case we must find the solutions of the following inequality:

[tex](x-3)(x+5)\leq0[/tex]

For [tex](x-3)(x+5)=0[/tex]we have the following solutions:

[tex]x=3\\x=-5[/tex]

As a possible solution we have the following intervals:

[tex]x\leq -5\\-5\leq x\leq 3\\x\geq 3[/tex]

We must choose a value included in each of the possible intervals, replace them in the original inequality and verify if it is fulfilled.

  • [tex]x\leq -5[/tex]

[tex](-6-3)(-6+5)\leq 0\\-9*-1\leq0\\ 9\leq0[/tex]

It is not true

  • [tex]-5\leq x\leq 3[/tex]

[tex](0-3)(0+5)\leq 0\\-3*5\leq 0\\-15\leq0[/tex]

It is true.

ANswer:

Option C